2015
DOI: 10.1111/1750-3841.12808
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Different Black Raspberry Confection Matrices Designed for Delivery of Phytochemicals

Abstract: Three forms of confections containing black raspberries (BRB) powder were developed to provide controlled release of phytochemicals for oral disease prevention. Our objective was to investigate the impact of varying confection matrices on the release rate of BRB phytochemicals. Confections were developed and prepared. Textural properties of confections were analyzed, compared and correlated with the release rate of phytochemicals from BRB confections with in vitro dissolution test. In the results, BRB content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
(52 reference statements)
1
17
0
Order By: Relevance
“…Sucrose was selected as a sweetener since sugar alcohols and fructose may alter microbiota composition [29], which could confound interpretation by masking the benefits of GTE. Confections will be prepared as described [[30], [31], [32]]. To deliver 1 g GTE, 6 confections (~4 cm 3 and ~16 g each) will be consumed; 2 with each daily meal.…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Sucrose was selected as a sweetener since sugar alcohols and fructose may alter microbiota composition [29], which could confound interpretation by masking the benefits of GTE. Confections will be prepared as described [[30], [31], [32]]. To deliver 1 g GTE, 6 confections (~4 cm 3 and ~16 g each) will be consumed; 2 with each daily meal.…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…In addition, there is interest and active research focused on developing novel products for delivering food-based agents targeting cancer prevention which may offer alternative modes or matrices of delivery, especially to highly accessible targets. As an example, pectin and starch based black raspberry confections retain 93% of original anthocyanins compared to only 60% in a hard candy confection designed to delivery phytochemicals [45]. …”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In a previous study, SEM experiments were also conducted on pectin and starch based soft candies. 36 It was also observed that pectin based soft candies had a rougher structure than the starch-based ones at a magnification of ×2500 due to the presence of sucrose in the pectin-based candies.…”
Section: Scanning Electron Microscopymentioning
confidence: 95%